Splicing Properties of Natural Fiber for Producing Yarns and Their Blends: A Review Paper - Mohamed Ben Hassen; Muhammad Awais; Faouzi Sakli; Saoussen Zannen; Mohammad Kanan (Journal of Natural Fibers)
Splicing stands as the preeminent technique employed for the seamless joining of yarn fibers. In stark contrast to traditional knotting methods, splicing achieves a level of seamlessness that closely mirrors the inherent structure of the yarn itself. The evolution of splicing techniques witnessed a significant breakthrough, resulting in the development of three distinct methodologies: pneumatic, mechanical, and electrostatic splicing. Among these, pneumatic splicing emerged as the frontrunner, owing to its exceptional performance when measured against its counterparts. The effectiveness of splicing lies in the appearance and mechanical attributes. These properties of a splice serve as the prerequisite in determining its overall quality. However, it is worth noting that comprehending the intricacies of splice structures, particularly within the intricate context of yarn fiber structures, poses a formidable challenge. This has necessitated a slew of experimental research endeavors, undertaken with the intent of unraveling the properties inherent to splicing. These investigations delve into the multifaceted interplay between yarn characteristics, splice parameters, and their collective impact on the quality of spliced yarn. In the forthcoming review article, we shall embark on a comprehensive exploration of various research papers within the domain of mechanical properties and the visual allure of splicing techniques.